Effect of Sodium Ion Concentration on Hydrogen Production from Sucrose by Anaerobic Hydrogen-producing Granular Sludge - 郝小龙 周明华 俞汉青 沈琴琴 雷乐成 (Chinese journal of chemical engineering, 2006)
This work evaluated the effects of sodium ion concentration, ranging from 0 to 16000mg-L- /(Na+), on the conversion of sucrose to hydrogen by a high-activity anaerobic hydrogen-producing granular sludge. At the optimum sodium ion concentration [1000-2000mg.L-1(Na+)] for hydrogen production at 37 deg C, the maximum sucrose degradation rate, the specific hydrogen production yield and the specific hydrogen production rate were 393.6 - 413.1mg.L-1-h-1, 28.04-28.97m1?-1, 7.52-7.83m1-g- 1.h-1, respectively. The specific production yields of propionate, butyrate and valerate decreased with increasing sodium ion concentration, whereas the specific acetate production yield increased, meanwhile the specific production yields of ethanol and caproate were less than 55.3 and 12.6mg-g-1, respectively. The hybrid fermentation composition gradually developed from acetate, propionate and butyrate to acetate with the increase in sodium ion concentration.